RNG1 is a Late Marker of the Apical Polar Ring in Toxoplasma gondii - Tran, Johnson Q. (2010)
The asexually proliferating stages of apicomplexan parasites cause acute symptoms of diseases such as malaria, cryptosporidiosis and toxoplasmosis. These stages are characterized by the presence of two independent microtubule organizing centers (MTOCs). Centrioles are found at the poles of the intranuclear spindle. The apical polar ring (APR), a MTOC unique to apicomplexans, organizes subpellicular microtubules which impose cell shape and apical polarity on these protozoa. Here we describe the characteristics of a novel protein that localizes to the APR of Toxoplasma gondii which we have named ring-1 (RNG1). There are related RNG1 proteins in Neospora caninum and Sarcocystis neurona but no obvious homologs in Plasmodium spp., Cryptosporidium spp. or Babesia spp. RNG1 is a small, low-complexity, detergent-insoluble protein that assembles at the APR very late in the process of daughter parasite replication. We were unable to knock-out the RNG1 gene, suggesting that its gene product is essential. Tagged RNG1 lines have also allowed us to visualize the APR during growth of Toxoplasma in the microtubule-disrupting drug oryzalin. Oryzalin inhibits nuclear division and cytokinesis although Toxoplasma growth continues, and similar to earlier observations of unchecked centriole duplication in oryzalin-treated parasites, the APR continues to duplicate during aberrant parasite growth.